How Do Library Clients Use Discovery Systems? - Wells, David; Richardson, Chris (LIANZA, 2014)
Resource discovery systems like Primo and Summon have developed rapidly over the last few years and have now largely established themselves as the industry standard - at least for research libraries - replacing the 'traditional' OPACs of the previous systems development cycle. The discovery systems have often been presented as inspired by internet search engines and social media, aspiring to provide library clients with a universal search and discovery experience, realising the previously illusory goal of the unified 'single search interface', and at the same time allowing for a personalised and interactive engagement between information seekers on the one hand, and library-curated resources on the other. But how far does the actual experience of discovery system users reflect the expectations of system vendors and library administrators? To date there have been few studies to examine this question. The present paper results from a research project into the use of the Primo discovery system at Curtin University conducted with the aim of understanding information seeking behaviour better in order to inform the development of systems. The paper focuses on questions of rationale and project design, and offers some preliminary findings.